The The Effect of Green Transformational Leadership on Corporate Entrepreneurship at PT Imago Randau Harmoni: - Rizqi Saputra , Raden Muhammad Iqbal; Kusumawati, Riny (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Batulayang Tourism Village is located on Jalan Sultan Hasanuddin, Batu Layang, Cisarua District, Bogor Regency. The village has two hamlets, four neighborhood associations, and twenty-three neighborhood associations. Because each region has different tourism potential, Batulayang Tourism Village has its own uniqueness in developing and assessing this potential. The purpose of this research is to examine the application of the Pentahelix model involving the government, community, entrepreneurs, media, and academics in Batulayang Tourism Village in developing tourism potential. The approach used in this research is qualitative. The sampling technique used in this research is purposive sampling. In addition to data collection methods, documentation, interview, and observation procedures were also used. The results showed that the growth of Batulayang Tourism Village with the pentahelix model was not ideal and the potential synergy of the actors had not been realized.